2007
DOI: 10.1038/sj.leu.2404769
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion kinase is required for CXCL12-induced chemotactic and pro-adhesive responses in hematopoietic precursor cells

Abstract: Hematopoietic stem/progenitor cells (HSC/P) reside in the bone marrow in distinct anatomic locations (niches) to receive growth, survival and differentiation signals. HSC/P localization and migration between niches depend on cell-cell and cell-matrix interactions, which result from the cooperation of cytokines, chemokines and adhesion molecules. The CXCL12-CXCR4 pathway, in particular, is essential for myelopoiesis and B lymphopoiesis but the molecular mechanisms of CXCL12 action remain unclear. We previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 52 publications
8
53
0
1
Order By: Relevance
“…1). Our data are also consistent with other studies that have shown that ␤-arrestins (12, 13) and FAK (32) are involved in CXCR4-promoted cell migration. Here, we establish that STAM1 is also required.…”
Section: ␤-Arrestin1⅐stam1supporting
confidence: 93%
See 2 more Smart Citations
“…1). Our data are also consistent with other studies that have shown that ␤-arrestins (12, 13) and FAK (32) are involved in CXCR4-promoted cell migration. Here, we establish that STAM1 is also required.…”
Section: ␤-Arrestin1⅐stam1supporting
confidence: 93%
“…The ␤-Arrestin1⅐STAM1 Complex Regulates FAK Autophosphorylation-Next, we set out to identify the signaling pathway by which the ␤-arrestin1⅐STAM1 complex mediates chemotaxis. We focused on FAK, a non-receptor tyrosine kinase involved in CXCR4-dependent chemotaxis of hematopoietic precursor cells (32,33). First, we determined whether FAK is necessary for CXCR4-promoted chemotaxis of HeLa cells.…”
Section: Disruption Of the ␤-Arrestin1⅐stam1mentioning
confidence: 99%
See 1 more Smart Citation
“…The tips of F-actin filaments are the sites of attachment of focal adhesion complexes. The activation of focal adhesion kinase by SDF-1 plays an important role in adhesion of hematopoietic precursor cells (47) and results in cytoskeleton rearrangements (33,47,48). Association of CXCR4 with the tips of F-actin filaments correlates with the reported stimulation of focal adhesion kinase by SDF-1 and suggests that the receptor might be a part of large macromolecular complexes assembled at the points of focal adhesion.…”
Section: Discussionmentioning
confidence: 89%
“…FAK is involved in the chemokine-induced adhesion of B cell progenitors (34), and Pyk2 is required for chemokine-induced migration of mature B cells (25). However, the role of these kinases in BCR-and integrin-induced B cell spreading has not been investigated, and the signaling pathways that link the BCR and integrins to tyrosine phosphorylation of Pyk2 and FAK have not been elucidated.…”
Section: Antibodies (Abs)mentioning
confidence: 99%